Overview of the application of informed consent in family planning services - Suryani, Eka; Diniyah, Kharisah (Universitas 'Aisyiyah Yogyakarta, 2023)
The results of the study of the patient safety management team in Indonesia for health services revealed that the provision of informed consent in various healthcare institutions needs to be optimal. Most health workers only ask patients and families to sign informed consent without providing a detailed explanation. This condition certainly affects the knowledge of patients and families. Knowledge of patients and families can cause problems if desirable things happen. This study aimed to describe the application of informed consent in family planning services at Anisa Yogyakarta Independent Midwife Practice (PMB). This study used descriptive qualitative methods. The sampling technique using snowball sampling technique amounted to 4 midwife informants and four acceptor informants. The results of in-depth interviews conducted with four midwife informants said that the implementation of informed consent in family planning services at the Independent Midwife Practice (PMB) had gone well. The midwife had carried out the obligation to ask for consent and provide information while for the completeness of filling out informed consent, 14 informed consent filled in, as many as eight informed consent and six incomplete informed consent and from in-depth interviews, the acceptor was able to explain the contents of the informed consent. Acceptor informants said they signed the action consent sheet after the midwife explained about family planning (KB) that acceptors would use. The informed consent application in family planning services at the Independent Midwife Practice (PMB) has generally been done well. Still, the completeness of filling out informed consent has yet to be maximized, and acceptors generally understand informed consent in family planning services.